2018
DOI: 10.4103/ortho.ijortho_379_17
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors, and Management of Infection Following Anterior Cruciate Ligament Reconstruction Surgery

Abstract: Background:Infection after anterior cruciate ligament reconstruction surgery (ACLRS) is a rare complication. Although there are number of studies from various Caucasian population but only few studies are available from Asian population. The aim of the study is to assess the incidence, risk factors and, clinical outcome using our treatment protocol.Materials and Methods:Out of 1468 arthroscopic ACLRS, 26 patients with clinical suspicion of infection were critically analysed in terms of laboratory reports of ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Indeed, postsurgical infection after osteosynthesis has an incidence of 0.5–10% for closed fracture [ 54 ] and up to 50% for open fractures [ 55 ]. It occurs in 1–14% of patients after spine surgery [ 56 ] and has similar incidence for several orthopedic and trauma procedures involving implantable devices [ 57 ]. The socioeconomic burden and management of such infections are incredibly challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, postsurgical infection after osteosynthesis has an incidence of 0.5–10% for closed fracture [ 54 ] and up to 50% for open fractures [ 55 ]. It occurs in 1–14% of patients after spine surgery [ 56 ] and has similar incidence for several orthopedic and trauma procedures involving implantable devices [ 57 ]. The socioeconomic burden and management of such infections are incredibly challenging.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled analysis showed that the mean time from surgery to the onset of surgical site infection symptoms was 17.1 days (95% CI, 13.2 to 21.0 days; I 2 =77%) ( online supplemental A5 ). The sensitivity analysis found that Gupta et al 25 was the main source of the heterogeneity, and the I 2 was reduced to 38% after the study was removed. A pooled analysis of the remaining studies showed that the mean time from surgery to the onset of surgical site infection symptoms was 18.4 days (95% CI, 15.2 to 21.6 days).…”
Section: Resultsmentioning
confidence: 99%
“…It is speculated that the main source of the heterogeneity was the difference in the study population. Gupta et al 25 is the only study from an Asian population (India), while the remaining studies are from European and US populations.…”
Section: Resultsmentioning
confidence: 99%
“…13 Post-surgical infection following spine surgery occurs in 1% to 14% of patients, depending on the preoperative diagnosis and type of surgery; 14,15 similar figures are reported for a variety of surgical procedures involving implantable devices in orthopaedics and trauma. 16-18…”
Section: The Impact Of Implant-related Infections In Orthopaedics Andmentioning
confidence: 99%